Access to railway stations and its potential in increasing rail use - Brons, M; Givoni, M; Rietveld, P (Elsevier, 2009)
The propensity to travel by rail and not, for example by car, can be considered to be a factor of the rail service offered, the access to it and the characteristics of the population served. Efforts to increase rail use usually focus on the rail service itself while the accessibility of the rail network receives less attention. In this context, the paper has two broad aims. First, to evaluate how important the ‘access-to-the-station’ part of a rail journey is to passengers in their overall satisfaction with the rail journey and second, to investigate the balance between characteristics of the service, the access to it and the population served in determining rail use in different parts of the rail network. The analysis is carried out for the Netherlands. To achieve the first aim, we use the Dutch Railways customer satisfaction survey and apply principal component analysis and derived importance techniques to assess the relative importance of accessibility in determining the overall satisfaction with the rail journey. For the second aim, we use regression analysis to explain, at the Dutch postcode level, the propensity to use rail. We find that satisfaction with the level and quality of the access to the station is an important dimension of the rail journey which influences the overall satisfaction from that journey and that the quality and level of accessibility is an important element in explaining rail use. The conclusion reached is that in many parts of the rail network improving and expanding access services to the railway station can substitute for improving and expanding the services provided on the rail network and that it is probably more cost efficient when the aim is to increase rail use. These parts of the network are mainly in the periphery where the current level of rail service is relatively low.